The Method of Finding High-Runner Products in the Assortment - Czerniachowska, Kateryna (Metoda wyszukiwania produktów o wysokiej sprzedaży, 2023)
Customers receive value from the products available at distribution centres or warehouses. Therefore different assortment optimisation practices are required. The goal of the research was to propose an approach to assortment optimisation that makes it possible to identify the high-running products in the warehouse, distribution centre, or retail space. The main feature which distinguishes it from other methods is that it allows determining high-runners in a particular place, using actual sales data or data from competitors when the sales data are unavailable. The proposed approach of product performance evaluation could be used by distribution organizations to implement an optimal pricing strategy. The developed technique is also suggested for enhancing the assortment to boost sales and assist the distributor or retailer in achieving their business goals.
Czerniachowska, K. (2023). The method of finding high-runner products in the assortment. W: H. Dudycz, M. Hernes, M. Pondel, A. Rot (red.), Informatyka w zarządzaniu (s. 52-65). Wrocław: Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu.
Keywords: assortment; high-runner; retail store; warehouse; distribution centre; asortyment; produkty o wysokiej sprzedaży; sklep detaliczny; magazyn; centrum dystrybucji